Prior residence, territory quality and life-history strategies in juvenile Atlantic salmon (Salmo salar L.) - Cutts, C. J.; Brembs, Björn; Metcalfe, N. B.; Taylor, A. C. (Blackwell Publishing, 1999)
Three groups of juvenile salmon were introduced sequentially into an artificial stream to investigate the effects of prior residence on behaviour and territory choice. Almost half of the first group obtained and defended distinct territories, the other half being constrained to an area approximately the size of one large territory. All of the fish in the subsequent groups, bar one, were also constrained to the same site. Since the fish were of similar size, prior residence alone seemed to influence which individuals obtained territories. However, within the first group, the fish that obtained territories were larger and more aggressive. The territorial fish did not appear to choose the most profitable territories, although they had the greatest opportunity to do so. Since juvenile salmon emerge from their gravel nests fairly synchronously, a time constraint on site sampling is hypothesised: there may be a risk in taking time to sample sites, since these same sites may become occupied with conspecifics. However, fish with territories fed at faster rates than non-territorial fish, possibly because of reduced competition for prey items. Consequently, fish from the first group (containing most of the territorial fish) grew faster than the other two groups. Moreover, most of the territory holders, but only one of the non-territorial fish, reached the threshold size that increases their probability of smolting the following year. This suggests that ability to obtain a defensible territory, primarily through prior residence, influences the age at which juvenile salmon can migrate to sea.